2019
DOI: 10.1002/jcsm.12484
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of body composition parameters in gastric/gastroesophageal junction cancer patients from the EXPAND trial

Abstract: Background Body fat and/or muscle composition influences prognosis in several cancer types. For advanced gastric and gastroesophageal junction cancer, we investigated which body composition parameters carry prognostic information beyond well‐established clinical parameters using robust model selection strategy such that parameters identified can be expected to generalize and to be reproducible beyond our particular data set. Then we modelled how differences in these parameters translate into survival outcomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 37 publications
5
55
3
Order By: Relevance
“…The role of PMI as a prognostic factor for survival has been reported recently in gastrointestinal tumors. In Hacker's study on advanced gastric and gastroesophageal junction cancers, PMI was shown to be a significant predictor for OS (p = 0.003) but not for DFS using the multivariate Cox model [17]. In our study, PMI was a significant prognostic factor for OS and DFS when applying univariate Cox model; however, PMI was not an independent prognostic factor for OS or DFS when the multivariate Cox model was used.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…The role of PMI as a prognostic factor for survival has been reported recently in gastrointestinal tumors. In Hacker's study on advanced gastric and gastroesophageal junction cancers, PMI was shown to be a significant predictor for OS (p = 0.003) but not for DFS using the multivariate Cox model [17]. In our study, PMI was a significant prognostic factor for OS and DFS when applying univariate Cox model; however, PMI was not an independent prognostic factor for OS or DFS when the multivariate Cox model was used.…”
Section: Discussioncontrasting
confidence: 63%
“…In studies by Dohzono and Deng, it was suggested that paraspinal muscle was composed of multifidus and erector spinae [19,20]. In other studies, multifidus and erector spinae combined with either psoas muscle [27], quadratus lumborum [17], or psoas muscle/quadratus lumborum [15,25,26] were defined as paraspinal muscles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of patient variables such as age, performance status, and neutrophil/lymphocyte ratio have been identi ed as prognostic factors for overall survival in the last decade [5][6][7] . Recently, the prognostic value of preoperative sarcopenia and nutritional status have been gaining emphasis 8,9 . However, we have been impressed that progressive skeletal muscle loss after gastrectomy might also be a powerful prognostic indicator based on thousands of cases of practice in our dedicated gastric cancer center.…”
Section: Introductionmentioning
confidence: 99%